Five-Month Observation of Persistent Diabetic Macular Edema after Intravitreal Injection of Ozurdex Implant - Dominik Zalewski; Dorota Raczyńska; Krystyna Raczyńska (Hindawi Limited, 2014)
Aims. This retrospective analysis was aimed at evaluating the effectiveness of treatment of persistent diabetic macular edema with intravitreal injections of 0.7 mg dexamethasone implant Ozurdex. The study comprised three male patients (6 eyes). Results. The average thickness of the retina at baseline was 632 μm, the medial BCVA was 0.8 logMAR, and corrected intraocular pressure was 13.7 mmHg. The maximum decrease in mean retinal thickness was observed at four weeks following the treatment and was 365 μm (−267 μm) and visual acuity improved by an average of two lines and was 0.6 logMAR. The largest increase in mean retinal thickness to average of 528 μm (+164 μm) occurred at 16 weeks and the average BCVA was 0.614 lines BCVA logMAR. In one eye, there was a steroid cataract development after the third dose of dexamethasone implant of 0.7 mg. Conclusions. The intravitreal dexamethasone implant treatment of patients with persistent diabetic macular edema in whom laser photocoagulation proved to be ineffective and as a result they required a monthly injection of anti-VEGF factors (Ranibizumab, Bevacizumab) may be a good alternative to extending the interval of injections. However, reinjections involve a high risk of developing poststeroid cataracts, which is not without significance in middle-aged patients.